Studying the performance of dielectric barrier discharge and gliding arc plasma reactors in tomato peroxidase inactivation. (March 2017) - Khani, Mohammad Reza; Shokri, Babak; Khajeh, Khosro
Abstract: Plasma as a promising technology has recently drawn considerable interest for decontamination of food and food processing at low temperature. Also, some conventional methods are used to prevent the changes in product quality with stopping their enzymatic activity. In this paper, two plasma systems were used to study a novel method in enzyme deactivation. First a DBD system was used to process the tomato extract and determine the processing time and gas type (air and helium). Later, a gliding plasma system was used, first time, for direct processing of both sides of tomatoes due to the low penetration of DBD plasma into the product and restrictions on its formation. In the optimum case, processing time was investigated as the most important parameter and, within 7 min, the enzyme residue percentage reached 4.84%. Comparison of plasma technology with other blanching methods indicated higher plasma efficiency during the processing time. The product temperature reached the maximum 40 °C during the plasma processing, which prevented the destruction of product's nutrient content. This study proves the capability of cold plasma technology for inactivating of enzymes. Graphical abstract: Practical application : Peroxidase activity causes vitamin C destruction. Also, it causes carotene bleaching and color change of anthocyanin. At the same time, it degrades unsaturated fatty acids and, thus, makes oxidation flavors in the product. In the industry, peroxidase deactivation is performed in hot water and steam and nutritional, sensory, and physical adequacies of the product are destroyed in thermal methods due to high temperature. In the present work, plasma technology is investigated for the first time to peroxidase inactivation in low temperature as an emerging technology. Highlights: For the first time, Plasma was processed tomato directly. The plasma causes the inactivation of peroxidase enzyme by more than 90 percent. Hunter lab test showed no significant change in color of the product. In this article two plasma reactor was used. Plasma performance with other enzyme inactivation methods such as boiling water, steam and microwave were compared.